Heart rate variability is related to training load variables in interval running exercises - Kaikkonen, P.; Hynynen, E.; Mann, T.; Rusko, H.; Nummela, A. (European Journal of Applied Physiology, 2012)
Overload principle of training states that training load (TL) must be sufficient to threaten the homeostasis of cells, tissues, organs and/or body. However, there is no "golden standard" for TL measurement. The aim of the present study was to investigate if post-exercise heart rate variability (HRV) could be used to evaluate TL of interval running exercises with different intensities and durations. Thirteen endurance-trained men (35 ± 5 years) performed MO250 [moderate intensity, 2 × 6 × 250 m/rec 30 s/5 min at 85% of the maximal velocity of the graded maximal test (V max)], MO500 (2 × 3 × 500 m/rec 1 min/5 min at 85% V max) and HI250 (high intensity, 2 × 6 × 250 m/rec 30 s/5 min at 105% V max) interval exercises on a treadmill. HRV was analyzed during rest, exercise and immediate 15 min recovery. Fast recovery of LFP (P < 0.001), HFP (P < 0.01) and TP (P < 0.01) occurred during the first two recovery minutes after each exercise. Strong negative correlations (P < 0.01) were found between post-exercise HRV and perceived exertion as well as excess post-exercise oxygen consumption. Post-exercise HRV differentiated interval exercises of equal work, but varying intensity or distance of running bout. The results of the present study suggest that immediate post-exercise HRV may offer objective information on TL of interval exercises with different bout durations and intensities.